2013
DOI: 10.3109/13816810.2013.811270
|View full text |Cite
|
Sign up to set email alerts
|

Familial Exudative Vitreoretinopathy caused by a Homozygous Mutation inTSPAN12in a Cystic Fibrosis Infant

Abstract: Familial exudative vitreoretinopathy (FEVR) is a genetic disease affecting the vascularization of the peripheral retina. The clinical manifestations are very heterogeneous, ranging from mildly affected patients, who could present no visual defects, to severe conditions which can also cause complete blindness at birth or in the first decade. FEVR can be inherited in all the three genetic forms: dominant, recessive and X-linked. To date, four genes have been associated with the condition: TSPAN12. NDP. FDZ4 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…FEVR can be caused by mutations in NDP, FZD4, LRP5, TSPAN12 , and ZNF408 – a zinc finger protein recently implicated in vascular biology (Collin et al, 2013; Nikopoulos et al, 2010b). TSPAN12 mutations have been predominantly reported in autosomal dominant FEVR (Kashani et al, 2014b; Kondo et al, 2011; Nikopoulos et al, 2010a; Poulter et al, 2010; Yang et al, 2011 Xu 14) but also in homozygous patients with an autosomal recessive inheritance pattern (Gal et al, 2014; Poulter et al, 2012; Savarese et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…FEVR can be caused by mutations in NDP, FZD4, LRP5, TSPAN12 , and ZNF408 – a zinc finger protein recently implicated in vascular biology (Collin et al, 2013; Nikopoulos et al, 2010b). TSPAN12 mutations have been predominantly reported in autosomal dominant FEVR (Kashani et al, 2014b; Kondo et al, 2011; Nikopoulos et al, 2010a; Poulter et al, 2010; Yang et al, 2011 Xu 14) but also in homozygous patients with an autosomal recessive inheritance pattern (Gal et al, 2014; Poulter et al, 2012; Savarese et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…In literature on Italian FEVR patients, only three genetic association studies describing a total of six probands are reported [1315]. Here, we present the results of clinical and genetic characterization of the largest Italian FEVR population, consisting of six probands and ten relatives, as a contribution to the FEVR disease molecular epidemiology in our country.…”
Section: Introductionmentioning
confidence: 93%
“…Interestingly, the tetraspanin 12 protein (TSPAN12), expressed in the retinal vasculature, phenocopies the depletion of FZD 4 , LRP5 and Norrin (Junge et al, 2009). As with FZD 4 and LRP5, several TSPAN12 mutations are associated with familial exudative vitreoretinopathy (Gal et al, 2014;Knoblich et al, 2014;Savarese et al, 2014;Ye et al, 2010). Although the mechanism is not fully understood, TSPAN12 selectively mediates Norrin over WNT-3A signaling indicating a possible role for conveying ligand selectivity to the FZD 4 /LRP5 receptor complex.…”
Section: Required Transmembrane Components As Cofactors (Tspan12 Gprmentioning
confidence: 97%